Dance exposure, general health, sleep and injury in elite adolescent Irish dancers: A prospective study - Cahalan, R.; Bargary, N.; O`Sullivan, K. (Physical Therapy in Sport, 2019)
Appropriate load management is lacking in elite adolescent Irish dancers. Monitoring of general health in these dancers is advocated to prevent injurydancers, and should be monitored carefully. Young Irish dancers ,may continue to dance when injured. Reasons may be benign or harmful, and should be monitored closely.